If it's not what You are looking for type in the equation solver your own equation and let us solve it.
h+1=6h+1-5h
We move all terms to the left:
h+1-(6h+1-5h)=0
We add all the numbers together, and all the variables
h-(h+1)+1=0
We get rid of parentheses
h-h-1+1=0
We add all the numbers together, and all the variables
=0
h=0/1
h=0
| 23x=-30 | | -255=3d | | 17x+21+57=180 | | 5x+71=-14 | | {2}{3}x=-30 | | 5.x-70=216-8.x | | 3f-23=10 | | 9m+3=-5 | | −2(−3x+8)=6(x+4)−3 | | 2/3(9x-6)=9 | | -4t=116 | | -4x-7(-3x-6)=135 | | -6(5k+3)=-18-k | | 3/2(8x-4)-4(2x-3)=-10 | | 360=5x+91-2x | | 21x-2=x+8 | | -2.5x-5=9 | | 2x-12=15x-4x | | 12+-v=25 | | 53x+4=-25 | | 3f+(-7)=(-1) | | -x/3+4=-2 | | x/3=x/2-5/4 | | -11=k/4 | | X+31=130+x+21 | | 15=n/(-4)+17 | | 14+31=-5(6x-9) | | -1/2m+1/2=1/10m-1/2 | | 7n+2(3n−4)=−8−3n | | 24a=-4(10-9) | | 3400t+600=t | | -36=12y-24 |